Effect of plasma and/or yeast extract on performance and intestinal morphology of piglets from 7 to 63 days of age - Rigueira, Leandro César Milagres; Thomaz, Maria Cristina [UNESP]; Rigueira, Dalton César Milagres; Pascoal, Leonardo Augusto Fonseca; Amorim, Alessandro Borges [UNESP]; Budiño, Fábio Enrique Lemos (FapUNIFESP (SciELO), 2013)
The objective of this study was to evaluate the effect of diets supplemented with plasma and/or yeast extract on performance (daily weight gain [DWG], daily feed intake [DFI] and feed conversion [FC]) and intestinal morphology of piglets from 7 to 63 days of age. A total of 288 piglets aged 7 days and weighing 2.57±0.05 kg were studied. A randomized block design consisting of four experimental diets, six repetitions and 12 piglets per experimental unit was adopted. The pre-starter I (7 to 21 days), pre-starter II (22 to 35 days) and starter I (36 to 49 days) diets were supplemented as follows: control diet (CD): no plasma or yeast extract; plasma (PL) diet: addition of 6%, 4% and 2% plasma; yeast extract (YE) diet: addition of 6%, 4% and 2% yeast extract; plasma + yeast extract (PL+YE) diet: addition of 3%, 2% and 1% plasma and yeast extract each. From 50 to 63 days of age all piglets received the same diet. No difference in performance was observed from 7 to 21 days and from 7 to 28 days of age, whereas DWG was higher from 7 to 35 days in piglets receiving the PL+YE diet (268, 278, 271 and 288 g/day for CD, PL, YE and PL+YE, respectively). From 7 to 49 days and from 7 to 63 days, DWG (330 and 519 g/day, respectively) and DFI (307 and 647 g/day) were higher in animals receiving the PL-YE diet when compared with those consuming CD (DWG: 295 and 486 g/day; DFI: 266 and 594 g/day). No significant differences in intestinal morphology were observed between piglets receiving the different diets. The combination of plasma and yeast extract elevates DWG, but does not affect the intestinal morphology of piglets from 7 to 63 days of age. © 2013 Sociedade Brasileira de Zootecnia.
Keywords: Feed conversion; Feed intake; Swine; Villi; Weight gain